Proton or photon? Comparison of survival and toxicity of two radiotherapy modalities among pediatric brain cancer patients: A systematic review and meta-analysis - Renáta Kiss-Miki; Mahmoud Obeidat; Vanda Máté; Brigitta Teutsch; Gergely Agócs; Szilvia Kiss-Dala; Péter Hegyi; Janka Kovács; Andrea Párniczky; Eszter Tuboly; Miklós Garami (PLoS ONE, 2025)
Background With the introduction of new therapy modalities and the resulting increase in survival rates, childhood brain cancers have become a focal point of research in pediatric oncology. In current protocols, besides surgical resection and chemotherapy, radiotherapy is required to ensure optimal survival. Our aim was to determine which of the two major irradiation options, proton (PT) or photon (XRT), was the least harmful yet effective for children with brain tumors. Methods The protocol was registered on PROSPERO in advance (CRD42022374443). A systematic search was performed in four databases (MEDLINE via (PubMed), Embase, Cochrane Library, and Scopus) on 23 April 2024. Odd ratios (OR) and mean differences (MD) with 95% confidence intervals (CI) were calculated using a random-effects model. Survival and six major types of side effects were assessed based on data in the articles and reported using the Common Terminology Criteria for Adverse Events (CTCAE) version 5.0. Heterogeneity was assessed using Higgins and Thompson’s I2 statistics. Results Altogether, 5848 articles were screened, of which 33 were eligible for data extraction. The 5-year overall survival results showed statistically no significant difference between the two radiotherapy modalities (OR = 0.80, 95% CI: 0.51–1.23, p = 0.22, I2 = 0%). In terms of toxicity rates, an advantage was found for PT, particularly in terms of chronic endocrine side effects (hypothyroidism OR: 0.22, 95% CI: 0.10–0428, p = 0.002, I2 = 68%), neurocognitive decline (global IQ level MD: 13.06, 95% CI: 4.97–21.15, p = 0.009, I2 = 68%). As for hematological, acute side effects, neurological changes and ophthalmologic disorders PT can be beneficial for survivors in terms of reducing them. Conclusions In comparison with XRT, PT can reduce most side effects, without significantly decreasing the survival rate. There is considerable clinical relevance in the findings, even not all of them are statistically significant, which may facilitate the development of protocols regarding the usage of radiotherapy methods, and may encourage the establishment of more proton centers, where more studies can be done.